Chapter 48 Christian reconceptualizations of citizenship and freedom in the Latin West - Rose, Els (Taylor & Francis, 2023)
The Roman city in late antiquity underwent dramatic changes in urban identity, economic activity, and socio-religious functions. Ancient city centres lost much of their dominance to the necropolis around the saint's tomb that developed into a centre of pilgrimage and religious settlements. While the cult of the saints transformed urban geography, it also redefined the identity of citizens. In this process, belonging to the civic community became more closely related to religious belonging. The ancient Latin vocabulary of citizenship underwent fundamental semantic changes when applied to the civic community defining itself now as 'fellow-citizens' of the local patron saint. Through the many performative expressions of the cult of the saints, most notably the hagiographic narrative and the liturgical cult, the great deeds of the saints and their relevance to the city and its inhabitants were re-enacted by the local religious lay and clerical community as well as by many visiting pilgrims. On their way home, pilgrims took elements of the cultic performance with them so that the originally local cult spread and gave rise to the foundation of new commemorative communities. The performative texts in commemoration of urban saints form a rich source to analyze how civic belonging and the Christianization of civic concepts transformed through performance. At the same time, by liturgically enacting the life and deeds of the urban patron saint, the citizens gave expression to the boundaries of their citizenship, demarcating the identity of those who belonged as well as those who did not belong to the civic community. The present chapter will analyze the inclusive and exclusive power of hagiographic texts and liturgical rites celebrating the life and deeds of saints, in order to gain deeper insight into the transformation of civic identities under the influence of Christianity in the late Roman and early post-Roman period.